'Blitz information', 1941 (1941)
1941 1939-1945 "'Blitz information', 1941" [HFR0215], 1941 This critical article by Tom Harrison, founder of the social research organisation, 'Mass Observation', accuses the Ministry of Information and local councils of failing to disseminate information and emergency advice and support to homeless people after air raids. The article is from Local Government Service, the journal of the National Association of Local Government Officers [ NALGO ] August 1941.